The Arp2/3 inhibitory protein Arpin is dispensable for chemotaxis. (7th March 2017) - Dang, Irène; Linkner, Joern; Yan, Jun; Irimia, Daniel; Faix, Jan; Gautreau, Alexis
Abstract : Arpin is a protein that inhibits the Arp2/3 complex at the leading edge of migrating cells and thus decreases the lamellipodial lifetime. Arpin provides a means to regulate directional persistence and allows the cells to turn. Here we found that, surprisingly, chemotaxis of Arpin‐depleted cells is not impaired. This holds true in mammalian cells and in Dictyostelium amoeba. Abstract : Arpin is an Arp2/3 inhibitory protein, which decreases the protrusion lifetime and hence directional persistence in the migration of diverse cells. Arpin is activated by the small GTPase Rac, which controls cell protrusion, thus closing a negative feedback loop that renders the protrusion intrinsically unstable. Because of these properties, it was proposed that Arpin might play a role in directed migration, where directional persistence has to be fine‐tuned. We report here, however, that Arpin‐depleted tumour cells and Arpin knock‐out Dictyostelium amoeba display no obvious defect in chemotaxis. These results do not rule out a potential role of Arpin in other systems, but argue against a general role of Arpin in chemotaxis.